2022
DOI: 10.3389/fmolb.2022.834651
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Low, Ultra-low, and Novel Complementary Biomarkers: Expanding the Spectrum of HER2 Positivity in Breast Cancer

Abstract: HER2 status in breast cancer is assessed to select patients eligible for targeted therapy with anti-HER2 therapies. According to the American Society of Clinical Oncology (ASCO) and College of American Pathologists (CAP), the HER2 test positivity is defined by protein overexpression (score 3+) at immunohistochemistry (IHC) and/or gene amplification at in situ hybridization (ISH). The introduction of novel anti-HER2 compounds, however, is changing this paradigm because some breast cancers with lower levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 97 publications
(141 reference statements)
0
45
1
Order By: Relevance
“…To our knowledge, this is the rst study to show the effect of HER2 status on response to NET in ER-positive breast cancer. In our cohort, HER2-lowpositive tumors comprise 84% of ER-positive breast cancer, which is higher than what was reported in most previous studies ranging 50%-65% 9,13 . could potentially be contributed by population difference as most earlier studies were conducted in the Caucasian population while our study included only the Chinese population.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…To our knowledge, this is the rst study to show the effect of HER2 status on response to NET in ER-positive breast cancer. In our cohort, HER2-lowpositive tumors comprise 84% of ER-positive breast cancer, which is higher than what was reported in most previous studies ranging 50%-65% 9,13 . could potentially be contributed by population difference as most earlier studies were conducted in the Caucasian population while our study included only the Chinese population.…”
Section: Discussioncontrasting
confidence: 60%
“…mRNA expression of ERBB2 in HER2-low-positive tumor is 1.4-fold of that in HER2-zero tumor in HR-positive breast cancer 10 . Differences between HER2low-positive tumors and HER2-zero tumors in terms of clinical and molecular features have been reported 9,[11][12][13] . Regarding the response to different treatments, the NSABP-47 trial showed that breast cancer with HER2-low-positive status did not bene t from adjuvant trastuzumab treatment 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Hormone receptors (HR) (i.e., estrogen receptor (ER), progesterone receptor (PgR)), Ki67, and HER2 status were updated to the breast biomarker reporting guidelines v1.4.1.1 published by the College of American Pathologists in November 2021 [ 29 , 30 , 31 ]. Then, lymphocyte subtyping was performed by immunohistochemistry (IHC) using antibodies against PD-L1 (clone 22C3), forkhead box P3 (FOXP3), CD4, and CD8 on an automated staining platform (i.e., Dako Omnis, Agilent, Santa Clara, CA, USA) on 4 µm-thick TMA sections, as previously described [ 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…HER2 protein expression status by IHC ranges from 0 to 3 + , with HER2 IHC scores of 0 reported as HER2-negative breast carcinomas, and HER2 IHC score of 3 + reported as HER2-positive breast carcinomas [ 17 ]. Currently, breast cancer with HER2 IHC score of 1 + or 2 + and negative FISH result defines as HER2-low breast cancer [ 18 , 19 ]. HER2 FISH testing measures the exact number of copies of the HER2 gene per nucleus and the ratio between the HER2 gene and a control probe to determine HER2 amplification status.…”
Section: Introductionmentioning
confidence: 99%